Factors Associated with Safe Sexual Behavior Among MSM Living with HIV: A Scoping Review - Theophylia Melisa Manumara; Kusman Ibrahim; Urip Rahayu (Green Publisher Indonesia, 2024)
Background: Human Immunodeficiency Virus (HIV) is a virus that attacks lymphocytes, leading to a gradual decline in the body's immune system and increasing susceptibility to various diseases, including Acquired Immunodeficiency Syndrome (AIDS). Men who have sex with men (MSM) are at a higher risk of contracting HIV/AIDS due to unsafe sexual behavior. Objective: This scoping review aims to explore the factors associated with safe sexual behavior in MSM Living with HIV. Method: The scoping review is based on the framework by Arksey and O'Malley. A literature search involved various databases, such as EBSCO, PubMed, Science Direct, and CINAHL I, with the keywords: